ENTERTAINMENT MEDIA AND THE CRISIS OF COMMUNICATION ETHICS IN AMBIGUOUS PHENOMENA (CASE STUDY OF PUBLIC FIGURE FEUD) - Aliffarazzi Syaqki Parmadie; Baarrafizki Dilkindi Parmadie (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: The thing that is of concern here is that the feud that the public figure is showing then propagates to television as the mass media, while there is a possibility that the spectacle of this feud contains bad values that are not good for society. Cases that occur are also considered contrary to existing communication ethics. Another unfortunate thing is the reason why several public figures are competing with each other to take action like this so that it becomes a trend, and this is directly proportional to the interest of the Indonesian people to see this feud. The feud was also considered as entertainment for the community. According to data, internet users in Indonesia have reached 212 million in January 2023. This means that around 77% of Indonesia's population has used the internet. Research methods: In this study the descriptive analytical method of phenomena was used to study an object in the context of people's behavior, conditions, systems of thought, and events at the present time. The approach method is a case study to reveal and describe the phenomenon of the subject and object of research on entertainment media and the crisis of communication ethics in the ambiguous phenomenon of public figure feud. Findings: Public figures should be able to realize that they are in the spotlight in public spaces. Their communication in public spaces should be able to display self-control abilities, maturity in attitude, and responsibility in speech and behavior. Implications: On the other hand, good understanding and awareness is needed by the public so that they are wiser in using the mass media. That way, there will be no shift in people's behavior in viewing communication ethics. Because, if we think about culture in Indonesia, it actually teaches good ways of communicating with others, without hurting or harming other parties.